Metabolomic profiles investigation on athletes` urine 35 minutes after an 800-meter race - Sun, T.; Wu, Y.; Wu, X.; Ma, H. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The aim of this study was to identify possible biological pathways of the metabolite profile changes in athletes' urine samples before and after 800-m runs.